UJI AKTIVITAS ANTIPIRETIK ESTRAK ETANOL AKAR GANTUNG BERINGIN (Ficus benjamina Linn) PADA TIKUS PUTIH JANTAN (Rattus norvegicus) YANG DIINDUKSI PEPTON 10% - Kenedy Marpaung, Jon; Suharyanisa; Tarigan, Yenni Gustiani (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2020)
Banyan hanging root (Ficus benjamina Linn) is a plant that has medicinal properties. Banyan hanging root (Ficus benjamina Linn) contains flavonoid substances that are able to inhibit prostaglandins so that they have antipyretic activity.  This study aims to test the antipyretic activity of banyan hanging root (Ficus benjamina Linn) against male white rats (Rattus norvegicus) induced peptone 10%.  This study is an experimental study with a Complete Randomized Design (RAL). The test animal used was a male white rat (Rattus norvegicus) which had been adapted for 1 week and was satisfied for ± 18 hours and was only given to drink ad libitum. The male white rats used were 15 heads with a body weight of 150–200 g. The test animals were divided into 5 groups in a randomized way, namely the Negative Control group (CMC 1%), the Positive Control group (Paracetamol 45 mg) and the test group, namely the administration of banyan hanging root ethanol extract (Ficus benjamina Linn) at a dose of 200 mg / Kg BB, 400 mg / Kg BB, and 600 mg / Kg BB. Each group consisted of 3 rats. Each of the test animals will be given pepton 10%.  Temperature measurements are carried out before the administration of peptone 10%, 1 hour after administration of pepton 10% and once every 30 minutes after treatment until the 180th minute. The data obtained were analyzed using the ANOVA test and continued with the Tukey HSD test.  A 180-minute study showed that banyan hanging root ethanol extract had antipyretic effects at a dose of 200 mg/Kg BB, a dose of 400 mg/Kg BB, and the most effective dose at a dose of 600 mg/Kg BB.  That the ethanol extract of the hanging root of banyan (Ficus benjamina Linn) has antipyretic activity in male white rats (Rattus norvegicus).